2016
DOI: 10.1128/jcm.01382-16
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Automated Flow Cytometry-Based Leukocyte Counts To Rule Out Urinary Tract Infection in Febrile Children: a Prospective Cross-Sectional Study

Abstract: A diagnosis of urinary tract infection (UTI) requires at least 18 h until confirmation of a positive urine culture (1, 2). The growing need to enhance the performance of urine culture combined with the need to free up resources by rejecting negative samples quickly and economically has drawn attention to tests that can be used as initial diagnostic tests to rapidly rule out UTI in a two-tiered diagnostic process (3). For that purpose, several rapid urinary tests are commonly used, including dipstick biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In this study, there were significant differences on HBP, IL-6, PCT, leukocyturia, and bacteriuria levels between UTI patients with positive culture, UTI patients with negative culture and healthy control group with p value <0.05. The results were consistent with several studies showing that there was a significant increase of IL-6, HBP, PCT, leukocyturia, and bacteriuria levels in patients with UTI compared with healthy control with p-value <0.05 (Kjolvmark et al, 2014;Duong et al, 2016;Manoni et al, 2009 The result of urine positive culture mostly dominated by gram negative bacterial infection as much 86.27 %, while infection of gram-positive bacteria as much 15.69%. The most common bacteria in this study were Escerichia coli (31.37%) followed by Staphylococcus epidermidis (13.73%) and Pseudomonas stutzeri (13.73%).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, there were significant differences on HBP, IL-6, PCT, leukocyturia, and bacteriuria levels between UTI patients with positive culture, UTI patients with negative culture and healthy control group with p value <0.05. The results were consistent with several studies showing that there was a significant increase of IL-6, HBP, PCT, leukocyturia, and bacteriuria levels in patients with UTI compared with healthy control with p-value <0.05 (Kjolvmark et al, 2014;Duong et al, 2016;Manoni et al, 2009 The result of urine positive culture mostly dominated by gram negative bacterial infection as much 86.27 %, while infection of gram-positive bacteria as much 15.69%. The most common bacteria in this study were Escerichia coli (31.37%) followed by Staphylococcus epidermidis (13.73%) and Pseudomonas stutzeri (13.73%).…”
Section: Resultssupporting
confidence: 91%
“…Study by Peters et al (2013) showed that an Asian population had higher levels of IL-6 than Europe population (Peters et al, 2013). In developing countries, especially Southeast Asia, the level of infectious disease is high to affect the response of individual infections (Duong et al, 2016). Second, the types of germs that cause infections may be impact on result of this study.…”
Section: Resultsmentioning
confidence: 72%
“…A positive urinalysis was defined as a trace or greater result for leukocyte esterase and/or nitrite on dipstick (Medi-test Combi 11; Macherey-Nagel, Düren, Germany), and/or the presence of ≥35 leukocytes/μL of uncentrifuged urine using the automated flow cytometer Sysmex UF-100 (Merck-Eurolab, Leuven, Belgium) ( 14 ). The laboratory staff was blinded to clinical information.…”
Section: Methodsmentioning
confidence: 99%
“…Seventy-eight records were retrieved from the electronic database, while 25 studies[13141516171819202122232425262728293031323334353637] were retained for qualitative synthesis [Figure 1]. The researchers had studied 11 individual tests and 7 combinations of various tests [Figure 1].…”
Section: Resultsmentioning
confidence: 99%